Pengembangan LKPD berbasis Problem Based Learning pada Materi Asam Karboksilat dan Ester untuk Kelas XII SMA/MA - Tiara Fauziah; Suryelita Suryelita (Universitas Negeri Padang, 2019)
Carboxylic Acid and Esther in second semester of 3rd grade High School was transferred to first semester due to the student’s final exam, so the learning process was uneffective. Therefore it needs a 2013’s curriculum compatible teaching materials as carboxyl acid and esther student worksheet which help students study independently. The aim of this research are to develop a PBL student worksheet and obtain its validity and practicality. The research using 4-D models: define, design, develop and disseminate, but the research was limited to develop stage. The research’s instrument are validity and practicality questionnaire given to lecturers, teachers and 3rd grade students. The results was analyzed by Kappa Cohen Formula and gets a very high category. The validity from lecturers and teachers get 0,87 point, teacher’s and student’s practicality get each 0,93 and 0,83 point.